Sparse Real Estate Ranking with Online User Reviews and Offline Moving Behaviors - Fu, Yanjie; Ge, Yong; Zheng, Yu; Liu, Yanchi; Xiong, Hui; Yuan, Nicholas Jing (Proceedings of the IEEE International Conference on Data Mining, 2014)
Ranking residential real estates based on investment values can provide decision making support for home buyers and thus plays an important role in estate marketplace. In this paper, we aim to develop methods for ranking estates based on investment values by mining users opinions about estates from online user reviews and offline moving behaviors (e.g., taxi traces, smart card transactions, check-ins). While a variety of features could be extracted from these data, these features are intercorrelated and redundant. Thus, selecting good features and integrating the feature selection into the fitting of a ranking model are essential. To this end, in this paper, we first strategically mine the fine-grained discriminative features from user reviews and moving behaviors, and then propose a probabilistic sparse pairwise ranking method for estates. Specifically, we first extract the explicit features from online user reviews which express users opinions about point of interests (POIs) near an estate. We also mine the implicit features from offline moving behaviors from multiple perspectives (e.g., direction, volume, velocity, heterogeneity, topic, popularity, etc.). Then we learn an estate ranking predictor by combining a pairwise ranking objective and a sparsity regularization in a unified probabilistic framework. And we develop an effective solution for the optimization problem. Finally, we conduct a comprehensive performance evaluation with real world estate related data, and the experimental results demonstrate the competitive performance of both features and the proposed model.